Investigation of the Effect of Yarn Waste Fibers and Cocamide Diethanolamide Chemical on the Strength of Hot Mix Asphalt (Fracture and Structural Integrity, 2022)
In this study, conventional bitumen test were performed on bituminous binder modified with Cocamide Diethanolamide chemical at different ratios. According to results of tests, the most suitable additive ratio has been determined as 5%. However, it was concluded that indirect tensile strength and resistance to moisture of samples prepared with bituminous binder modified with 5% Cocamide Diethanolamide has been adversely affected. It was desired to investigate that whether these properties could be strengthened by yarn waste fibers. Firstly, the effect of 0.1%, 0.2% and 0.3% yarn waste fibers on samples prepared with reference bituminous binder was investigated. Obtained results showed that both indirect tensile strength and resistance to moisture of samples containing 0.1% yarn waste fiber increased. Therefore, 0.1%, 0.2% and 0.3% yarn waste fibers were added to the aggregate mixture and mixing of them with bituminous binder modified with 5% Cocamide Diethanolamide were provided. According to obtained results, different ratios of yarn waste fibers added to aggregate mixture did not have a positive effect on moisture sensitivity. Tensile strength ratio values of samples containing bituminous binder modified with 5% Cocamide Diethanolamide and yarn waste fibers added to the aggregate mixture did not provide specification limit.
Keywords: Cocamide Diethanolamide; Yarn waste fiber; Superpave; Moisture Sensitivity